Diseño de un modelo de gestión para la optimización de procesos de contratación pública en Gobiernos Autónomos Descentralizados (GAD) de Ecuador. - González Roa, Jonathan David (2025)
The present research, entitled "Design of a Management Model for the Optimization of Public Procurement Processes in Decentralized Autonomous Governments (GAD) of Ecuador," has the general objective of designing a management model that improves efficiency and strengthens transparency in public procurement processes at the local level. The study is based on an in-depth diagnosis of the regulatory, technical, and operational deficiencies faced by GAD, particularly during the preparatory and pre-contractual stages, identifying limitations in planning, training, use of technological tools, and process standardization. Methodologically, a mixed approach was adopted, comprising both quantitative and qualitative components: quantitative, through surveys administered to 150 officials from different Ecuadorian regional governments, and qualitative, through interviews with public procurement experts. A review of the regulations applicable to public procurement in Ecuador was also conducted. Techniques such as descriptive statistics, content analysis, and thematic categorization were used. The results reveal a low perception of regulatory efficiency and clarity, limited ongoing staff training, a lack of flowcharts and digital tools, and limited transparency. In response, an applicable and scalable management model was designed, based on process-based management theories, national and international legislation, and principles of efficiency, effectiveness, and internal control. It is concluded that the proposed model is a viable tool for strengthening decentralized public management, promoting good contractual practices, and contributing to the institutional development of Ecuadorian GAD.